Addition of Clonidine Increases Duration and Magnitude of Vasodilative Effect Induced by Sympathetic Block With Mepivacaine in Dogs. Issue 4 (1st July 2001) - Kimura, Yoshiyuki; Hamaguchi, Shinsuke; Okuda, Yasuhisa; Kitajima, Toshimitsu
Abstract : Background and Objectives: The aim of this study is to examine the duration and magnitude of vasodilative effect induced by sympathetic block with the addition of clonidine to mepivacaine. Methods: We measured mean arterial pressure (MAP), heart rate (HR), and right and left brachial artery blood flow (BABF) before and after stellate ganglion block (SGB) in dogs. The experimental protocol was designed as follows: (1) left SGB using 1.0 mL 0.5% mepivacaine (n = 6) and (2) left SGB using the addition of clonidine 0.5 μg to 1.0 mL 0.5% mepivacaine (n = 6). Results: MAP and HR did not change significantly throughout the study in either group. Left SGB with mepivacaine increased left BABF significantly from 10 minutes through 50 minutes after SGB (baseline, 100%; peak at 10 minutes after SGB, 176% ± 28%; P < .01). Left SGB with the addition of clonidine to mepivacaine induced a significant increase of left BABF from 10 minutes through 70 minutes after SGB (baseline, 100%; peak at 10 minutes after SGB, 223% ± 42%; P < .01). The values of left BABF after SGB with the addition of clonidine to mepivacaine were significantly higher than those of SGB with mepivacaine alone from 10 minutes through 80 minutes after SGB ( P < .05). Right BABF decreased significantly after SGB throughout the study in both groups. Conclusions: The addition of clonidine increases both duration and magnitude of the vasodilative effect induced by sympathetic block over that caused by mepivacaine alone.